Agronomic performance and chemical composition of silage from corn hybrids grown in southern Rondonia (Research, Society and Development, 2021)
Corn is a widely used crop for silage. However, due to the changes introduced in recent genotypes, regional information related to the agronomic production behavior and the chemical composition of the silage produced becomes necessary for the appropriate technological development destined to agricultural and animal production in the Amazon region. With this premise, the present study aimed to evaluate the agronomic performance of corn hybrids cultivated for silage production and the chemical composition of the ensiled material. The experiment was conducted from October 2020 to March 2021, under field conditions, in the experimental area of the Federal Institute of Education, Science and Technology of Rondonia, Colorado do Oeste Campus, in the municipality of Colorado do Oeste, RO, Brazil. The experimental design used was completely randomized, composed of six corn hybrids (GNZ7210 VTPRO2, AG8480 VTPRO3, BM3073 VTPRO3, BM270 VTPRO2, BM3066 VTPRO3 and BM3077 VTPRO3) and five replicates, cultivated at spacing of 0.80m between rows and 0.20m between plants. There was variation in the agronomic performance of the commercial corn hybrids for the southern region of Rondônia. The silages produced from the six corn hybrids showed bromatological and chemical characteristics that characterize them as silages of very good quality, despite showing significant differences in the percentages of DM, MM, CP, N-NH3/TN, NDF and ADF. The hybrid BM3073 PRO3 stood out for fresh matter yield, shoot N content and quality of the silage produced, which may result in the reduction of silage production costs.